Evaluation of Lung and Bronchoalveolar Lavage Fluid Oxidative Stress Indices for Assessing the Preventing Effects of Safranal on Respiratory Distress in Diabetic Rats - Saeed Samarghandian; Reza Afshari; Aghdas Sadati (The Scientific World Journal)
We investigated the effects of antioxidant activity of safranal, a constituent of Crocus sativus L., against lung oxidative damage in diabetic rats. The rats were divided into the following groups of 8 animals each: control, diabetic, and three diabetic + safranal-treated (0.25, 0.50, and 0.75 mg/kg/day) groups. Streptozotocin (STZ) was injected intraperitoneally (i.p.) at a single dose of 60 mg/kg for diabetes induction. Safranal was administered (i.p.) from 3 days after STZ administration to the end of the study. At the end of the 4-week period, malondialdehyde (MDA), nitric oxide (NO) and reduced glutathione (GSH) contents, activity of superoxide dismutase (SOD), and catalase (CAT) were measured in the bronchoalveolar lavage fluid (BALF) and lung tissue. Safranal in the diabetic groups inhibited the level of MDA and NO in BALF supernatant and lung homogenate. The median effective dose (ED50) values were 0.42, 0.58, and 0.48, 0.71 mg/kg, respectively. Safranal in the diabetic groups increased the level of GSH and the activity of CAT and SOD in BALF supernatant and lung homogenate. The ED50 values were 0.25, 0.33, 0.26 in BALF and 0.33, 0.35, 0.46 mg/kg in lung, respectively. Thus, safranal may be effective to prevent lung distress by amelioration oxidative damage in STZ diabetic rats.